THE IMPACT OF THE LABOR GYMNASTIC PROGRAM IN THE INCREASE OF THE FLEXIBILITY: A STUDY REGARDING THE PROGRAM TO PUT IN PRACTICE WITH GARBAGE COLLECTORS OF NITEROI (Fiep Bulletin - online, 2011)
This study takes as a principal focus the checking of the increase of the flexibility as tool in the improvement of the quality of life of waste collectors in the city of Niteroi, Rio de Janeiro inside his environments of work, through to labor gymnastic program. Possible dysfunctions and injuries can be caused by the alteration of the flexibility. Besides injuries of other muscles lead to alterations biomechanics and consequent diversions postural, providing also pain. The used methodology went to the application of questionnaires and of the physical test; to sit and to reach, used in the evaluation of the flexibility of the lumbar column and of the hamstrings muscles. The lack of specific works regarding to labor Gymnastics is one of the problems found. The statistical analysis consisted of the use of the test t – gauged tuns samples, to compare the averages of the test of seating to reach, with level of signification α =0,05. Analyzing the results, we can observe a significant improvement of the flexibility of these individuals after training based on the labor gymnastics.
Keywords: Labor gymnastic; flexibility; training